Multi-Level Marketing Distributors and their Deceptive Advertising on Social Media: A Case Study of a Particular Multi-Level Marketing Company and their Distributors Operating in South Africa - Hopley, Rachel (The IIE, 2020)
Multi-level marketing (MLM) is a direct sales business model which has been built upon a system whereby individuals are rewarded for contributing to the sale of products or the delivery of services through a network of distributors (Failla, 1996). With the amount of deceptive marketing communications that online consumers are exposed to nowadays, the chances of finding a business opportunity that is authentic and genuine are very rare. This study investigates MLM firms and their recruiters’ and distributors’ use of advertising communications online, using a particular MLM company operating in South Africa as a case study. For the purpose of keeping this study ethical and protecting the identity of this company, it will be referred to as “Company A” in order to avoid damaging the company’s public image. Social media has become a popular channel for distributors to communicate with and recruit potential distributors; a downside to this is that lies and exaggerations have become more common. The purpose of this study is to explore the MLM industry from a South African perspective with regards to how the use of social media as a recruitment channel has led to deceptive marketing communications online. Furthermore, this study seeks to explore ways in which South African social media users can be more aware of deceptive marketing communications and able to identify these online. The methodology of this study took a qualitative approach, where exploratory data was collected in the form of an online survey as well as one-on-one online email interviews. The rich data and findings that were revealed in this study led to a deeper understanding of and insight into “Company A”, with real behaviours and opinions being shaped by both consumers and past recruiters and distributors who have personal experience with the brand. Various recommendations were given in order to assist MLM firms in coming up with a more ethical way to recruit potential distributors through social media. From the research conducted, it is understood that the online behaviours and activities of certain “Company A” distributors has had a negative impact on consumers, as many perceive MLM to be a pyramid scheme based on their individual experiences. “Company IV A” is an example of an MLM company that promises people across the globe an opportunity to gain financial independence; however, consumers are becoming more aware of unauthentic online business opportunities. This study contributes towards a deeper understanding of a modern South African perspective of MLM distributors and extends on existing research in terms of the ethical issues related to MLM firms.
Keywords: Social media; Direct sales; Marketing communication; Multi-level marketing